Lung segmentectomy with novel microwave surgical instrument (Acrosurg. Revo). Issue 4 (11th February 2021) - Mimura, Takeshi; Kamigaichi, Atsushi; Kagimoto, Atsushi; Yamashita, Yoshinori
Abstract: A novel model of a microwave surgical instrument (Acrosurg. Revo) which is an energy device using microwave technology and 2450 MHz microwave has recently been developed for endoscopic surgery. Herein, we describe the technique of pulmonary segmentectomy with a novel device.